A METHODOLOGY FOR TEACHING TECHNICAL TERMS IN ROBOTICS ON MOBILE PLATFORMS - Haydarova, Kamolakhon (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
One of the most important problems in the current technical education process is the lack of a convenient and fast resource for students to master technical terms . Especially in the teaching of modern disciplines such as robotics , many terms are in foreign languages, which makes it difficult for students to understand their content and apply them in practice. Due to the fact that the existing textbooks and manuals in the Uzbek education system do not provide information on these terms in a sufficiently interactive form, students have difficulty remembering them and applying them in practical activities. Therefore, in this article, to facilitate the learning of technical terms and digitize the educational process, a mobile dictionary application was developed using the MIT App Inventor platform. This application allows you to learn technical terms anywhere and anytime through popular mobile phones . The program includes the most commonly used terms in robotics, their translation, explanation, pronunciation, and visual images. The application was pilot-tested among students studying robotics at the elementary level. During the test, students’ technical terminology memorization, classroom activity, and motivation for independent learning were analyzed. The results showed that using a mobile dictionary has a positive effect on increasing educational efficiency , enhancing interactivity , and quickly and accurately mastering technical terms .